Hornbeam forests on the southern edge of their distribution (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Syntaxonomy of hornbeam forests on the boundary between forest-steppe and steppe zones of Right-Bank Ukraine is presented. The communities belong to the class Querco-Fagetea, to the order Fagetalia sylvaticae, to the union Carpinion betuli and 2 associations, four subassociations and two variants that are new and described for the first time. A comparative and cluster analysis together with phytoindication are applied for justifying description of new syntaxa. The analysis of results shows a sufficient difference between the hornbeam forests on southern edge of its natural distribution and typical hornbeam forests of forest-steppe zone.
Keywords: syntaxonomy, forest vegetation (sylva), edge, forest-steppe, steppe.